2017
DOI: 10.5812/jhealthscope.14176
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Malnutrition and Failure to Thrive in Children Under 2 Years of Age in Shahroud, Iran, in 2015

Abstract: Background: Malnutrition and failure to thrive (FTT) is a delay or a halt in children's growth, which leads to serious compilations if it is left untreated. Malnutrition due to its prevalence is the most important nutritional disease in developing countries and has the most prevalence among infants and preschool children. This study aimed at rating and determining the effective factors of malnutrition incidence and growth delay among 0 to 24 months children. Methods: To identify children under 2 years of age, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…Findings of this study, similar to other Iranian studies (18), indicated that mothers with pre-pregnancy Body Mass Index (BMI) of less than 18.5 were at 22.06 times greater risk of having children with FTT than those with normal BMI (P < 0.001). Contrary to some previous reports, this study did not show any significant relationship between pre-pregnancy overweightness and FTT among children (4,19,20).…”
Section: U N C O R R E C T E D P R O O Fsupporting
confidence: 80%
“…Findings of this study, similar to other Iranian studies (18), indicated that mothers with pre-pregnancy Body Mass Index (BMI) of less than 18.5 were at 22.06 times greater risk of having children with FTT than those with normal BMI (P < 0.001). Contrary to some previous reports, this study did not show any significant relationship between pre-pregnancy overweightness and FTT among children (4,19,20).…”
Section: U N C O R R E C T E D P R O O Fsupporting
confidence: 80%
“…Factors affecting malnutrition included age, birth weight, birth spacing, and the mother's BMI at child birth. Shimaa M. Koabar, et al 2018 [28]. Kafr El-Sheikh Governorate, Egypt.…”
Section: According To Egyptian National Nutritionmentioning
confidence: 99%
“…In addition, weight loss, overweight, and obesity accounted for 4.5%, 11%, and 8.2% of participants, respectively [26]. In Kafr El-Sheikh Governorate, a study reported that over-nutrition and obesity were the prominent malnutrition problem among studied group while wasting and underweight was affecting a minimum percentage of their number [28].…”
Section: According To Egyptian National Nutritionmentioning
confidence: 99%
“…Most of the studies presented HC in z-score (HCZ) according to HC-for-age z-score values proposed by the WHO 4 . However, two studies used national reference growth curves 12,13 , whereas the others used HC values in centimeters [14][15][16][17][18][19][20][21] .…”
Section: Main Outcome: Head Circumferencementioning
confidence: 99%